Construction of Aeromonas salmonicida subsp. achromogenes AsaP1‐toxoid strains and study of their ability to induce immunity in Arctic char, Salvelinus alpinus L. Issue 10 (1st October 2014) - Schwenteit, J M; Weber, B; Milton, D L; Bornscheuer, U T; Gudmundsdottir, B K
Abstract The metalloendopeptidase AsaP1 is one of the major extracellular virulence factors of A. salmonicida subsp. achromogenes, expressed as a 37‐kDa pre‐pro‐peptide and processed to a 19‐kDa active peptide. The aim of this study was to construct mutant strains secreting an AsaP1‐toxoid instead of AsaP1‐wt, to study virulence of these strains and to test the potency of the AsaP1‐toxoid bacterin and the recombinant AsaP1‐toxoids to induce protective immunity in Arctic char. Two A. salmonicida mutants were constructed that secrete either AsaP1E294A or AsaP1Y309F. The secreted AsaP1Y309F‐toxoid had weak caseinolytic activity and was processed to the 19‐kDa peptide, whereas the AsaP1E294A‐toxoid was found as a 37‐kDa pre‐pro‐peptide suggesting that AsaP1 is auto‐catalytically processed. The LD50 of the AsaP1Y309F‐toxoid mutant in Arctic char was significantly higher than that of the corresponding wt strain, and LD50 of the AsaP1E294A‐toxoid mutant was comparable with that of an AsaP1‐deficient strain. Bacterin based on AsaP1Y309F‐toxoid mutant provided significant protection, comparable with that induced by a commercial polyvalent furunculosis vaccine. Detoxification of AsaP1 is very hard, expensive and time consuming. Therefore, an AsaP1‐toxoid‐secreting mutant is more suitable than the respective wt strain for production of fish bacterins aimed to protect against atypical furunculosis.